Critical yield models to estimate the damage caused by leaf rust in white oat Modelos de ponto crítico para estimar danos causados pela ferrugem da folha da aveia branca - Reis E.M. (2008)
In field experiments carried out in the 1995 and 1996 growing seasons, the gradient of leaf rust intensity on the white oat cultivar UPF 13 was generated by spraying the above ground plant parts of the crop with different rates of the fungicide triadimenol. Damage equations were obtained relating grain yield and disease incidence at different growing stages. In the 1995 growing season the equations were: R= 2,103.5 -17.983I and R= 2,404.6 - 12.832I, for elongation and boot stage, respectively, and for 1996, R= 3,889.2 - 27.871I and R= 5,366.4 - 20.999I (where R= grain yield; I= disease as foliar incidence), for booting and flowering stages respectively. These equations, having the damage coefficient, may be used to calculate the economic damage threshold (LDE) as a criterion to indicate the moment for the fungicide application to control leaf rust in oats. Reductions in grain yield, hectoliter weight, and one thousand kernels weigh reached 57.13%, 16.64% and 21.49% respectively for the 1995 growing season and 19.79%, 13.39% and 16.33%, for the 1996 season.